American Crime Fiction
X, 146 p.
Keywords: This volume offers critical and theoretical perspectives on one of the most popular and enduring literary genres: American crime fiction. There are essays on Edgar Allan Poe, Dashiell Hammett, Raymond Chandler, James M.Cain, Mickey Spillane, George V. Higgins and Jerome Charyn, covering the period from 1840 to 1980. Hammett and Chandler have two essays each, reflecting their importance, and lasting influence on the genre. Each essay deals with a major aspect or concept associated with crime fiction. A variety of reading strategies are employed to interrogate these texts, illustrating both the range of approaches available and the fact that modern literary theory can usefully be applied to any text or genre. Students of crime fiction seeking new readings, and readers interested in modern approaches to literature, such as psychoanalytic theories, Marxist theory, semiotics, and linguistic theory, will find this book useful and informative. The essays are all new, and have been specially written for Insights by leading academics.